Delta‐shaped anastomosis vs circular stapler anastomosis after laparoscopic distal gastrectomy with Billroth I reconstruction: A randomized controlled trial. Issue 3 (9th December 2019) - Hosoda, Kei; Mieno, Hiroaki; Ema, Akira; Ushiku, Hideki; Washio, Marie; Song, Ildae; Watanabe, Masahiko; Yamashita, Keishi; Hiki, Naoki
Abstract: Introduction: The aim of this study is to evaluate the efficacy of delta‐shaped anastomosis compared to circular stapler anastomosis in laparoscopic distal gastrectomy with Billroth I reconstruction. Methods: This is a single‐center randomized controlled study. Eligibility criteria included histologically proven gastric adenocarcinoma in the lower third of the stomach, clinical stage I tumor. Patients were preoperatively randomized to circular stapler anastomosis or delta‐shaped anastomosis. The primary endpoint is the number of analgesics used during three days after surgery. We compared the surgical outcomes of the two groups. Postoperative quality of life was evaluated using the Postgastrectomy Syndrome Assessment Scale‐45. This trial was registered at the UMIN Clinical Trials Registry as UMIN000025160. Results: Between December 2016 and September 2018, 39 patients (delta‐shaped anastomosis 18, circular stapler anastomosis 21) were enrolled. There was no difference in the number of analgesics used during three days after surgery (median nine: delta‐shaped anastomosis vs nine: circular stapler anastomosis, P = .91). There was no difference in the overall proportion with in‐hospital grade II–IIIB surgical complications (11%: delta‐shaped anastomosis, 14%: circular stapler anastomosis). There was no operation‐related death in either arm. Regarding postoperative quality of life evaluated one month after surgery, diarrhea subscale was significantly worse in delta‐shaped anastomosis than in circular stapler anastomosis. Conclusion: We did not demonstrate the advantage of delta‐shaped anastomosis in terms of postoperative pain. Since delta‐shaped anastomosis tended to cause postoperative abdominal symptoms related to diarrhea, we should carefully apply the delta‐shaped anastomosis to laparoscopic distal gastrectomy with Billroth I reconstruction.